Relationship between Service Quality and Demographic Factors with Patient Satisfaction at the General Polyclinic of Manguharjo Public Health Center, Madiun City - Nurwijayanti; Ayu Elvita Bintama; Panca Radono (Journal Of Nursing Practice, 2025)
Background: Healthcare Manguharjo, a key primary facility in Madiun City, faces challenges like long wait times and limited referrals. Purpose: This study examines how service quality and demographics affect patient satisfaction, aiming to improve care and ensure equitable access for underserved communities. Methods: A cross-sectional survey of 91 patients used SERVQUAL questionnaires to assess five service quality dimensions. Spearman correlation examined relationships with demographics and satisfaction, ensuring ethical protocols and participant confidentiality. Results: Service quality moderately correlated with satisfaction (r=0.308, p=0.003). Demographics showed weaker but significant influence (r=0.258, p=0.013). Patients praised staff friendliness and efficiency but highlighted needs for improved communication (e.g., clearer medical instructions) and facility cleanliness. Service quality significantly drives satisfaction, while demographics play secondary roles. Strengthening communication, modernizing facilities, and reducing administrative delays are recommended to address gaps. Conclusion: Future studies should explore longitudinal impacts of these interventions. Prioritizing patient-centered improvements can enhance Healthcare Manguharjo’s community health outcomes.